ANALISIS IMPLEMENTASI STRATEGI SEKOLAH DALAM MENANAMKAN NILAI AGAMA DAN MEMBENTUK KARAKTER SISWA DI SD - Mufida, Elma; Fatimah, Siti; Iqbal, Muhammad; Adha, Nurul; Khotimah, Khusnul; Bunga Saddina, Risma; Suhaimi (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
Instilling religious and character values in elementary schools is crucial and requires appropriate implementation strategies. The main objective of this study is to describe and analyze the strategy of instilling religious and character values at SD Negeri Melayu 11 Banjarmasin. The study employs a qualitative descriptive approach with data collection techniques of triangulation (observation, interview, and documentation). The findings conclude that the strategy is implemented in an integrated manner through four key dimensions: habituation of routine religious activities, consistent role modeling from the school community, innovative local wisdom-based programs (Tatamba Akur, Jumat Berbagi), and synergistic roles among the principal, teachers, students, and parents. Religious activities were proven to have a significant impact on the formation of students' religious, moral, social, and confident character. Success is supported by school commitment and structured programs, but hindered by limited facilities and insufficient parental supervision.